Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1021/acsomega.0c01946
|View full text |Cite
|
Sign up to set email alerts
|

Humidity-Sensing Properties of a BiOCl-Coated Quartz Crystal Microbalance

Abstract: The performance of a bismuth oxychloride (BiOCl)-based quartz crystal microbalance (QCM) humidity sensor was studied using an oscillating circuit method. The BiOCl powder was prepared by a hydrolysis method. Scanning electron microscopy, X-ray diffraction, and Fourier transform infrared spectroscopy were used to characterize the BiOCl sample. Its humidity-sensing property was analyzed by combining it with a QCM at room temperature (25 °C). Experimental results indicated that the BiOCl-based QCM sensor showed g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 69 publications
(95 reference statements)
0
8
0
Order By: Relevance
“…They found that a thinner graphene oxide film provides a shorter response time and smaller sensitivity (Δ f per %RH), attributed to the mass loads of adsorbed water molecules. Chen et al recently reported a QCM-based humidity sensor for respiratory monitoring under the nose [ 114 ]. They used a bismuth oxychloride film having a hydrophilic surface as a humidity-sensitive layer.…”
Section: Types Of Fast-response Humidity Sensormentioning
confidence: 99%
“…They found that a thinner graphene oxide film provides a shorter response time and smaller sensitivity (Δ f per %RH), attributed to the mass loads of adsorbed water molecules. Chen et al recently reported a QCM-based humidity sensor for respiratory monitoring under the nose [ 114 ]. They used a bismuth oxychloride film having a hydrophilic surface as a humidity-sensitive layer.…”
Section: Types Of Fast-response Humidity Sensormentioning
confidence: 99%
“…In the past few decades, acoustic transducers including bulk acoustic wave (BAW) transducers, capacitive micromechanical ultrasonic transducers (CMUT), film bulk acoustic resonator (FBAR) transducers, and surface acoustic wave (SAW) transducers have been extensively developed in the field of gas and humidity sensing [ 8 , 9 ]. In particular, quartz crystal microbalance (QCM), as a typical BAW transducer, is a more desirable humidity transducer due to its ability to detect high sensitivity on the nanogram scale, simple structure, strong material selectivity, low cost, high interference immunity, and ability to withstand harsh environments [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, there have been advances toward fabricating humidity sensors that are capable of detecting humidity levels in exhaled breath. Typically, sensing is achieved by measuring with various transducing methods, including capacitance, 7 , 8 resistance, 9 , 10 absorbance, 11 13 surface acoustic waves, 14 17 and adsorption on quartz crystal microbalance, 18 21 and by devices such as a field effect transistor. 22 , 23 A variety of materials including conducting polymers, metal oxides, noble metal nanoparticles, carbon nanotubes, and graphene oxide have been investigated for their humidity-sensing capabilities.…”
Section: Introductionmentioning
confidence: 99%